PENGARUH ENDORSEMENT INFLUENCER DAN VIDEO PEMASARAN TERHADAP MINAT BELI PRODUK BODY LOTION SKINFLAIR DI MEDIA SOSIAL - Hidayah, Nurul; Andriyansyah, Muhammad Syarfan; Anansida, Hanif Haidar; Kusmayati, Nindya (Politeknik Bisnis Indonesia, 2025)
The goal of this study is to investigate how product reviews and marketing videos on the TikTok platform affect local consumers' intentions to buy Ventela brand shoes. With its captivating and dynamic visual content, TikTok, a social media site centered around short-form videos, has the ability to sway users. This study employs a quantitative method using IBM SPSS Version 3.0 and involves 57 respondents who are active TikTok users. Data was collected through questionnaires. The influence of each variable was tested using validity tests, partial tests (t-tests), and linear regression analysis. The results indicate that marketing video content has a positive and significant effect on purchase intention (significance value 0.001 < 0.05), while product reviews do not show a significant influence (significance value 0.253 > 0.05). Based on the linear regression test, the equation obtained is Y = 1.544 + 0.816X1 + 0.144X2 + e. These results show that, partially and concurrently, both factors significantly and favorably affect consumers' intentions to make purchases. Product appeal is increased by imaginative and educational marketing videos, and influencer endorsements have been shown to increase trust and emotional connection. These findings provide businesses with strategic recommendations for enhancing influencer partnerships and producing higher-caliber video content to impact consumer decisions.